1999
DOI: 10.1128/iai.67.1.455-459.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of the Neisseria gonorrhoeae lbpB Gene Product

Abstract: We cloned lbpB, encoding a predicted 80-kDa lipoprotein, upstream of lbpA. A nonpolar mutant (LbpB− LbpA+) had normal lactoferrin (LF) binding and grew normally with LF as an iron source, whereas LbpB− LbpA− and LbpB+LbpA− strains had reduced binding of LF and did not grow with LF as an iron source. LbpB bound LF directly in an affinity purification, suggesting that LbpB might play a still-uncharacterized role in the LF iron utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…To scavenge all traces of free iron for this assay, 2.5 M apo-lactoferrin was added to each culture after the initial 2-h growth period and dilution. Because strain FA1090 and its derivatives are unable to utilize lactoferrin as an iron source due to a natural deletion in the lactoferrin receptor (4,24), no iron was available for growth. If a utilizable iron source is then added to this medium, the bacteria regain the ability to grow.…”
Section: Methodsmentioning
confidence: 99%
“…To scavenge all traces of free iron for this assay, 2.5 M apo-lactoferrin was added to each culture after the initial 2-h growth period and dilution. Because strain FA1090 and its derivatives are unable to utilize lactoferrin as an iron source due to a natural deletion in the lactoferrin receptor (4,24), no iron was available for growth. If a utilizable iron source is then added to this medium, the bacteria regain the ability to grow.…”
Section: Methodsmentioning
confidence: 99%
“…All strains of N. meningitidis have the capacity to utilize haemoglobin, lactoferrin and transferrin (Marri et al, 2010). In contrast, approximately half of gonococcal isolates have undergone a large deletion in Iron import in pathogenic Neisseria 247 the locus encoding the lactoferrin-iron internalization system, rendering this system inactive (Biswas et al, 1999). Further, engineered gonococcal mutants unable to utilize lactoferrin and transferrin as iron sources were found to be avirulent in a human male infection model of gonococcal disease (Cornelissen et al, 1998), attesting to the importance of these iron transport systems in initiating infection and proliferating in humans.…”
Section: Iron Import Systems In Pathogenic Neisseriamentioning
confidence: 99%
“…The loss of Lf binding by NM and NG lbpA mutants, as assayed by solid-phase dot blot assays, indicated that LbpB alone did not mediate Lf binding (55,139). Liquid phase equilibrium binding assays confirmed the conclusion that LbpA is required for Lf binding (202). What, then, is the role of the LbpB lipoprotein?…”
Section: Lbpab (Lactoferrin Receptor)mentioning
confidence: 82%
“…What, then, is the role of the LbpB lipoprotein? Mutants lacking this receptor component exhibit reduced growth with Lf, a ~50% reduction in Lf binding capacity, and 55 Fe uptake rates 60% of wild-type LbpAB (55,202,203). These results suggest an important, but non-essential, role for LbpB in the binding and internalization of Lf-Fe.…”
Section: Lbpab (Lactoferrin Receptor)mentioning
confidence: 91%
See 1 more Smart Citation